Effect of spacer arm length between adhesion ligand and alginate hydrogel on stem cell differentiation. (30th March 2016) - Lee, Jae Won; Kim, Hwi; Lee, Kuen Yong
Highlights: Alginate hydrogels can be modified with ligands containing various spacer arms. Increasing spacer arm length enhances stem cell osteogenesis and adipogenesis. Spacer arm length influences stem cell chondrogenesis only at high cell density. Abstract: Controlling cell–polymer interactions is one of the most critical components in the development of scaffolds for tissue engineering. In this study, we hypothesized that controlling the spacer arm length of adhesion ligand, such as RGD peptide, coupled to alginate hydrogels could regulate stem cell phenotypes. The results of our investigation indicate that the viability of stem cells was enhanced as spacer arm length increased. The spacer arm length of adhesion ligand also influenced differentiation of stem cells. Osteogenic and adipogenic differentiation of stem cells was promoted by increasing adhesion ligand spacer arm length. On the contrary, chondrogenic differentiation was independent of spacer arm length at the same ligand density and cell concentration. Interestingly, as the cell concentration in alginate gels increased, the gels modified with adhesion ligand with long spacer arms improved chondrogenic differentiation of stem cells. We demonstrate here that the spacer arm length of adhesion ligand conjugated to polymer scaffolds is a key factor in controlling proliferation and differentiation of stem cells, which may be critical for many tissue engineering applications.